Foreign women authors under Fascism and Francoism : gender, translation and censorship - Godayol, Pilar, 1968-; Taronna, Annarita (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2018)
"This collection of essays highlights cultural features and processes which characterized translation practice under the dictatorships of Benito Mussolini (1922-1940) and Francisco Franco (1939-1975). In spite of the different timeline, some similarities and parallelisms may be drawn between the power of the Fascist and the Francoist censorships exerted on the Italian and Spanish publishing and translation policies. Entrusted to European specialists, this collection of articles brings to the fore the microhistory that exists behind every publishing proposal, whether collective or individual, to translate a foreign woman writer during those two totalitarian political periods. The nine chapters presented here are not a global study of the history of translation in those black times in contemporary culture, but rather a collection of varied cases, small stories of publishers, collections, translations and translators that, despite many disappointments but with the occasional success, managed to undermine the ideological and literary currents of the dictatorships of Benito Mussolini and Francisco Franco." -- Contraportada.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Publishers and publishing -- Italy -- History -- 20th century; Publishers and publishing -- Spain -- History -- 20th century; Women authors -- History -- 20th century; Translating and interpreting -- Italy -- History -- 20th century; Translating and interpreting -- Spain -- History -- 20th century; Language policy -- Italy -- History -- 20th century; Language policy -- Spain -- History -- 20th century; Censorship -- Italy -- History -- 20th century; Censorship -- Spain -- History -- 20th century; Editores y editoriales -- Italia -- Historia -- Siglo XX; Editores y editoriales -- España -- Historia -- Siglo XX; Mujeres autoras -- Historia -- Siglo XX; Traducción e interpretación -- Italia -- Historia -- Siglo XX; Traducción e interpretación -- España -- Historia -- Siglo XX; Política lingüística -- Italia -- Historia -- Siglo XX; Política lingüística -- España -- Historia -- Siglo XX; Censura -- Italia -- Historia -- Siglo XX; Censura -- España -- Historia -- Siglo XX; Libros electrónicos.